Enhanced permeability of high-frequency Nd2Fe17N3 magnetic powder with reduced surface iron oxide layer by inert gas annealing - Jun Akamatsu; Satoshi Abe; Ryoya Okazaki; Nobuyoshi Imaoka (AIP Advances)
Nd2Fe17N3 powder, coated with an outer α-Fe2O3 layer and inner phosphate rare earth compound layer through phosphoric acid coating and subsequent heat treatment in air, was formulated in our previous study. In this study, the resulting material is further heat treated in Ar for varying durations to investigate the enhancement in its properties. The results indicated an increase in magnetic permeability μ′ from 10.39 to 12.94 post heat treatment in Ar, whereas loss tangent tanδ remained constant at 0.01. Additionally, the outer α-Fe2O3 layer changed to Fe3O4 post Ar treatment, as confirmed by scanning transmission electron microscopy (STEM), X-ray diffraction (XRD), electron diffraction spectroscopy, X-ray photoelectron spectroscopy (XPS), and extended X-ray absorption fine structure analysis (EXAFS). This transformation was probably due to the reduction of the α-Fe2O3 layer, facilitated by the base material in the inert gas. Consequently, ferromagnetic coupling between the Nd2Fe17N3 and other particles was enhanced, while their electrical insulating properties were maintained. These findings suggest that our proposed process can facilitate the development of magnetic materials in the megahertz band.